The Enhancement of Student's Organizational Citizenship Behavior to Improve Organizational Embeddedness: An Action Research on Beijing Polytechnic in Beijing, China - Ma, Jun; Lu, LeeHsing (ABAC ODI JOURNAL Vision. Action. Outcome, 2023)
This action research aims to enhance students' organizational citizenship behavior (OCB) to improve organizational embeddedness in a vocational college. The sample size of this research was 59 sophomore students, 30 in the experimental group and 29 in the control group. They came from Beijing Polytechnic (BP), majoring in mechanical and electrical engineering (MEE). This study's questionnaire instrument has 24 items. After the 16-weeks-intervention program, the author collected pre-intervention and post-intervention data and used the quantitative method. The author used the Shapiro-Wilk (S-W) test that data is non-parametric. The study findings are: (H1a) The Spearman's test was applied, and there is a statistically significant relationship between OCB and organizational embeddedness. (H2a) The Wilcoxon signed-rank sum test was applied, and there is a statistically significant difference in OCB and organizational embeddedness before and after ODI. (H3a) The Mann-Whitney U test was applied, and the effect of OCB on organizational embeddedness was statistical significance. The qualitative analysis's findings supported the alternative hypotheses. The study concluded that after ODI, participants' OCB level and organizational embeddedness increased.